Hypotony Maculopathy: Clinical Presentation and Therapeutic Methods. Issue 2 (December 2015) - Thomas, Merina; Vajaranant, Thasarat; Aref, Ahmad
Abstract Introduction Hypotony maculopathy is ocular hypotony complicated by papilledema and/or folding of the retina and choroid in the posterior pole. Our objective was to examine the current literature regarding hypotony maculopathy and treatment methods. Methods A systematic review of the English-language literature was conducted by performing a broad search of PubMed from 1972 through 2015 using the keywords hypotony maculopathy and hypotony. Additional articles were identified from bibliographies of relevant articles. Results Hypotony maculopathy was infrequent before the introduction of antimetabolite agents in glaucoma-filtering surgery, and the incidence of this entity is now up to 20%. Risk factors for developing hypotony maculopathy include male gender, young age, myopia, and primary filtering surgery. Correctly identifying the etiology of hypotony is essential for successful treatment. Treatment of hypotony maculopathy includes procedures to elevate the intraocular pressure, thus reversing the collapse of the scleral wall and chorioretinal wrinkling. Conclusion This review discusses the definition, clinical presentation, pathophysiology, incidence and risk factors, prevention and treatment of hypotony maculopathy.